EDWARD SNOWDEN"S COMMUNICATION STRATEGY AGAINST INFORMATION DOMINATION GOVERNMENT OF THE UNITED STATES - Adrian Adzanas; Bambang Ipto (DIA: Jurnal Administrasi Publik, 2022)
This research explains how Edward Snowden disseminates data from the National Security Agency (NSA) secret program. As a result of Edward Snowden’s espionage action, Snowden received sanction from the United States Department of Justice to file criminal charges against Snowden. In its implementation, the results of the leakage have an important on distrust between the allies and the United States government. Allied countries and the international public are asking the United States government to reform the NSA to be more transparent. This research focuses on qualitative research methods. Data analysis in the form of data reduction, data display, drawing conclusions, and verification. The results showed Edward Snowden’s communication strategy against the dominance of information by the United States government was to join the board of the nonprofit organization Freedom of the Press Foundation. The media that includes the disclosure of crime leaked by Edward Snowden are known as The Intercept, which means the media focuses on the disclosure of crime by the state based on documents leaked by Edward Snowden.